Analysis on the Spatio-Temporal Characteristics of Urban Expansion and the Complex Driving Mechanism: Taking the Pearl River Delta Urban Agglomeration as a Case. (15th September 2020) - Liu, Luo; Liu, Jianmei; Liu, Zhenjie; Xu, Xuliang; Wang, Binwu
Abstract : Rapid urbanization on a global scale leads to a number of issues such as arable land occupation and ecological degradation. In this context, analyzing the driving mechanism of urban land expansion in complex urban systems facilitates sustainable urban development. Most relevant studies focused on the role of each driving factor and less considered the interaction between different factors spatially and temporally. In order to provide a deep insight into the complex driving mechanism of urban expansion, this study began with an analysis of the spatio-temporal characteristics of urban expansion in the Pearl River Delta (PRD) urban agglomeration in different periods. Then, the driving mechanism of urban expansion intensity (UEI) and urban expansion landscape pattern were analyzed, based on the interaction of different driving factors over space and time. The result showed as follows. (1) During the period of 2000–2008, the overall UEI in the PRD was higher than that of the period of 2008–2015. From 2000 to 2015, the most important source of urban land expansion was farmland, followed by forest land. Meanwhile, the decline in the proportion of outlying expansion type indicated that the urban land has gradually become more compact. (2) From 2000 to 2015, the socio-economic factors had a greater effect on UEI than natural factors. And the interaction between the pairs of factors on UEI during 2000–2008 was significantly stronger than that during 2008–2015. (3) The driving factors of the urban landscape expansion index during the period from 2008 to 2015 were far more powerful than 2000–2008. And the interaction between the pairs of factors on urban landscape expansion index during 2000–2008 was significantly stronger than that during 2008–2015.